THE DEVELOPMENT OF WEB BASED LEARNING MEDIA NETWORK AND COMPUTER BASIC AT SMK NEGERI 1 LEMBAH MELINTANG - Fauzi Fauzi; Hasan Maksum (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2020)
The purpose of this research is to produce a valid web-based learning media, practical, and effective in basic computer and networking subjects. This web-based learning media is designed to improve student’s understanding so that it can improve to learn the outcomes. The method in this study uses Research and Development (R and D) with 4-D development procedures (Define, Design, Develop, Desseminate). The data of analysis technique uses descriptive analysis techniques to describe the validity, practicality, and effectiveness of web-based learning media. The results obtained of this development research: The validity of web-based learning media is declared valid on the media and material aspects. The practicality of web-based learning media from teacher and student responses is stated to be very practical. The effectiveness of web-based learning media is stated to be effective in improve to learn the outcomes. Based on the findings of this study it is concluded that the web-based learning media is valid, practical, and effective to be used as a learning aid in basic computer and network subjects.